The Effects from Physical Exercise on the Blood Glucose Levels, HbA1c and Quality of Life of Type 2 Diabetes Mellitus Patients: A Systematic Review - Novita Fajriyah; I Ketut Sudiana; Erna Dwi Wahyuni (Universitas Airlangga, 2020)
Introduction: The present study aimed to analyze the effects of aerobic exercise, resistance and a combination of both on blood glucose levels, HbA1c and quality of life for patients with T2DM.Methods: This systematic review used PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). Scopus, Science Direct and PubMed online databases were extensively searched, focusing on the last five years. The search utilized the phrases